Integrated effects of poultry manure and chemical fertilizer on the growth, leaf yield and stevioside content of stevia - Zaman, MM; Chowdhury, MAH; Chowdhury, Tanzin (Journal of the Bangladesh Agricultural University, 2016)
Stevia is important for its leaves which are used as non calorie sweetener and also in many therapeutic applications including diabetes. The present investigation was carried out in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh to investigate the integrated effects of poultry manure (PM) and chemical fertilizer (CF) on the growth, leaf biomass yield and stevioside content of stevia grown in two contrasting soils (acid and non-calcareous) of Bangladesh. Six combinations of PM and CF viz. PM0+CF0, PM0+CF100, PM3+CF50, PM3+CF75, PM5+CF50, PM5+CF75 were used. The study revealed that PM along with different percentages of chemical fertilizers exerted significant influence on the growth, leaf yield and stevioside content of stevia. The highest values of all the parameters except stevioside were found from the plant receiving PM @ 3 t ha-1 along with 75% CF. The leaf biomass yield was 1088% and 867% higher in acid soil and non-calcareous soil, respectively, over control. Stevioside content was increased with increasing the levels of PM up to 5 t ha-1 and also with the advancement of growth period from 30 to 60 days after planting. The highest amount of stevioside (10.45%) was detected in the leaves of the plant that received PM @ 5 t ha-1 along with 75% CF at 60 DAP in acid soil and it was 9.11% in non-calcareous soil at the same period. The lowest values of all the parameters including stevioside content were obtained from the plant which received neither PM nor CF. Considering the overall performance, farmers may be advised to cultivate stevia in acid soil applying PM @ 3 t ha-1 along with 75% chemical fertilizer to boost up the production of stevia under the agro-climatic condition of the study area in the context of Bangladesh. J. Bangladesh Agril. Univ. 13(2): 175-182, December 2015